Following the threads of scenographic costume at PQ19. Issue 1 (15th May 2020) - Marshall, Susan
ABSTRACT: Scenographic costume is wearable scenography that has the ability to instigate performance and tell a story in its own right. The tradition of performance defining scenographic costume can be traced back to the theatrical experimentations of the artistic movements of the early twentieth century. At several points in history, scenographic costume has been used as a means to explore diverse social, cultural and political questions, and the different examples of scenographic costume at PQ19, as well as recent research by scholars such as Donatella Barbieri and Sofia Pantouvaki, prove that costume can still be a powerful and meaningful tool with which to explore and research a wide range of pertinent themes. Following the threads through the Prague Exhibition Grounds and the Industrial Palace, this article reflects on the subtle but omnipresent nature of scenographic costume at PQ19, where mushrooms popped up on heads, fish rushed in from the rain, and a plumber's skirt was inflated by singing housewives.